Christian Worldview Education in The Era of Disruption - Paultje Tampa; Jammer Prayerson Andalangi (Conference Series, 2020)
Existential questions for human existence has always been very important for everyone to answer. The increasing number of disturbances as well as innovation in all areas in this disruptive era makes existential questions about life increasingly important for Christians. This interest moves the researchers to investigate a worldview education model that fits Christians today. Therefore, the research focuses on the formulation and education of Christian worldview that The Apostle Paul used in his letter to the Colossians. The study used Bruner's paradigmatic and narrative theory of thought to analyze the explanatory approach that Paul used in presenting his Christian worldview in his letter to the Colossians. This research also used the grammatical historical contextual interpretation method to study the logical development of Paul's argument, the situation behind each of Paul's statements and different subgenres that he used in the letter. Based on the interpretation the researchers then formulated the existential concept of Paul and the contextual approach he used to disseminate his Christian worldview to the saints in Colossae. The results of this study found that Paul used a combination of paradigmatic and narrative methods to explain his Christian worldview as a way to address the problem of syncretism that occurred in the Colossian church. Paul based his existential concept of human life in the grace of God which was powerfully pictured through the supremacy of the life and work of Jesus Christ. Paul explains that a Christian worldview can only be gained through faith in the gospel of the grace of Jesus Christ. The research found eight principles that Paul used as a model for Christian worldview education. They are: 1) The need to cultivate prayer life and prayer models that focus on God’s grace and peace, 2) The need to formulate a Christian worldview that solely emerges and focus on the gospel of Christ, 3) Worldview dissemination can be done through the current technology available for the learner, 4) The declaration of the believers’ true identity in Christ by grace as a paradigm, 5) Teaching Christian paradigms on Christ’s supremacy can be done through song, poetry or prose, 6) The need to explain the relationship between God’s grace and human’s trust, 7) Embracing suffering as life facts by the power of Christ as the believers wait for the final glorification, and 8) Developing a counter explanation for philosophies that undermine Christ’s grace and supremacy based on the true identity of the believers in Christ.